Proposal for construction of learning object as support to the teaching of art - Américo, Marcos (2017)
The comprehensiveness of art as a language instituted and capable of serving the most diverse contexts, brings us to understand it as an area of knowledge, with its own codes and knowledge, which, being inserted in the school curricula, demands that it be updated to the contemporary environment of Education, integrating digital media as possible resources for expression and communication, redesigning the teaching of art in a contemporary way from the use of technology in the classroom. The research proposes the construction of a Learning Object conceptualized as any resource that can be used as support in the educational process and that offers the necessary digital support for the development of the proposed sequence in the search of a multidisciplinary and current learning for the Elementary Education in Art.